Composite material for automobile roof and preparation method of composite material
By setting up a barrier layer during the hot pressing composite process of PP fiber composite board, the problems of additives and spots caused by damage to the upper layer of adhesive are solved, and the effect of improving the appearance quality of the car roof and providing mechanical strength is achieved.
Patent Information
- Application Number
- CN202510258356.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-06
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-03-06
AI Technical Summary
During the hot pressing process of existing PP fiber composite boards, the upper adhesive film is prone to damage, causing additives to spread outward and adhere to the fabric layer of the car roof, forming spots, affecting the appearance quality.
A barrier layer is provided between the PP fiber/glass fiber mat and the upper adhesive film. The barrier layer is made of molded composite of PP adhesive film, maleic anhydride modified PP membrane, PA membrane, maleic anhydride modified PP membrane and PP adhesive film to play a protective role and prevent the diffusion of the additive.
It effectively reduces the penetration of additives into the fabric layer in PP fiber/glass fiber felt, prevents spots, improves the appearance quality of the car roof, and provides a certain mechanical strength for PP fiberglass boards.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of composite materials, and more specifically, to a composite material for automobile roof and a preparation method thereof. Background Art
[0002] As the current automotive interior decoration industry is increasingly moving towards high performance, environmental protection, low carbon, and low VOC, the requirements for car ceilings are also getting higher and higher. The car ceiling is a crucial structural component of the entire vehicle interior. In addition to its role in interior decoration, it can also effectively play a role in heat insulation and sound insulation.
[0003] The car roof is generally composed of a fabric layer, a substrate layer and a back non-woven fabric layer. The fabric layer faces the passengers and reflects the appearance of the roof. It is generally made of non-woven fabrics, knitted fabrics, PVC films, etc. The substrate layer is the main determinant of the other properties of the roof except for the appearance performance. It is generally made of PU fiberglass board, PP fiberglass composite board, corrugated cardboard, hemp fiberboard, etc. PP fiberglass composite board has the advantages of lightweight, low odor, low VOC, etc., and is increasingly widely used in automotive interior products, allowing car owners to have a more comfortable riding environment.
[0004] The current PP glass fiber composite board substrate structure consists of: a bottom non-woven fabric, a bottom adhesive film, a PP glass fiber felt and an upper adhesive film, and then the upper adhesive film is used to contact and bond with the non-woven fabric layer of the ceiling. During the board forming process, since the four sides of the car roof are mostly curved structures, the upper adhesive film has a large deformation during hot pressing and compounding, which makes the upper adhesive film easy to be damaged, causing the additives (such as antioxidants, etc.) in the PP glass fiber felt to emit outward and eventually adhere to the surface of the fabric layer on the front of the car roof, resulting in a mottling problem similar to white spots on the surface of the car roof, affecting the appearance quality of the car roof. Summary of the invention
[0005] In order to prevent the additives in the PP glass fiber felt in the PP glass fiber composite board from emitting outwards, thereby causing spots on the surface of the car roof and affecting its appearance quality, the present application provides a composite material for a car roof and a preparation method thereof.
[0006] In a first aspect, the present application provides a composite material for a car roof, which adopts the following technical solution: A composite material for automobile ceilings comprises a bottom non-woven fabric, a lower adhesive film, PP fiber / glass fiber felt, a barrier layer, an upper adhesive film and a fabric layer in sequence, wherein the barrier layer is formed by compression molding of a PP adhesive film, a maleic anhydride modified PP film, a PA film, a maleic anhydride modified PP film and a PP adhesive film in contact with each other in sequence.
[0007] By adopting the above technical solution, a barrier layer is arranged between the PP fiber / glass fiber felt and the upper adhesive film. When the upper adhesive film and the fabric layer are molded, the upper adhesive film is hot-melted to bond the fabric layer, and the barrier layer can play a protective role, which can prevent the additives in the PP fiber / glass fiber felt from emitting to the fabric layer through the damaged parts of the upper adhesive film, thereby reducing the mottling phenomenon on the car roof.
[0008] The outermost layer of the barrier layer is PP film, which can be bonded to the PP fiber / glass fiber felt and the upper film respectively. The PP film close to the upper film can play a bonding and protective agent diffusion effect when the upper film is damaged by hot pressing. The maleic anhydride modified PP film can improve the compatibility of the PP film and the PA film during hot melt bonding during compression molding, thereby improving the bonding strength between the PP film and the PA film, thereby obtaining a barrier layer with tightly bonded layers. The PA film can effectively block the penetration of small molecular substances such as antioxidants, thereby reducing the problem of car roof mottle caused by the penetration of antioxidants and other additives.
[0009] Optionally, the barrier layer has a thickness of 0.12-0.15 mm.
[0010] By adopting the above technical solution, a barrier layer of this thickness can effectively reduce the penetration of additives such as antioxidants in the PP fiber / glass fiber mat into the fabric layer, while providing a certain amount of mechanical strength for the PP glass fiber board.
[0011] Optionally, the PP fiber / glass fiber mat contains PP fibers and glass fibers in a mass ratio of 1:1.
[0012] By adopting the above technical solution and using appropriate PP fiber and glass fiber to prepare PP fiber / glass fiber mat, the tensile strength and bending modulus of the composite fiber mat are higher, the material is harder and tougher, and the performance remains stable at high temperatures. In addition, the shrinkage rate of the material is reduced and the dimensional stability is improved.
[0013] Optionally, the preparation method of the PP fiber / glass fiber mat is as follows: The glass fiber is immersed in silica sol, taken out and immersed in an anhydrous ethanol solution of graphene oxide, ultrasonicated at a power of 250-300W for 100-120min, then dried at 50-55°C under normal pressure, and needled to obtain a matrix felt; The polypropylene and cellulose acetate butyrate are mixed in a mass ratio of 1:0.1-0.2, and the mixture is melt-spun after vacuum drying. The spun product is extracted at 60-65° C. for 20-24 hours using acetone as a solvent to obtain PP fiber. The PP fiber is dispersed in the polyacrylamide solution to obtain a suspension, and the suspension is poured on a base felt, vacuum filtered and dried to obtain a PP fiber / glass fiber felt.
[0014] By adopting the above technical scheme, the glass fiber is impregnated with silica sol, and the viscosity of the silica sol is used to adhere graphene oxide. After normal pressure drying, the silica sol coated on the glass fiber forms a silica aerogel with rich porosity, so it has good sound absorption performance. The porous structure can make sound waves move back and forth, and the air near the pore wall moves fast or slow. When the air propagates in the pores inside the material, due to the vibration of the sound wave, the viscosity of the air particles will produce corresponding viscosity, so that the sound energy is converted into heat energy, thereby causing the attenuation of the sound wave, and the purpose of absorbing the sound wave is achieved; and the large number of hydroxyl groups on the surface of graphene oxide can undergo condensation reaction with the silicon hydroxyl groups of the glass fiber and the silica sol, so that the graphene oxide is firmly bonded to the surface of the glass fiber, making it difficult to peel off from the glass fiber. After adding graphene oxide, It can adhere to the surface and gaps of glass fibers. When sound waves enter the material, the air in the pores of the material vibrates due to the entry of the sound waves. At the same time, graphene oxide vibrates with the glass fibers under the action of sound waves and air vibrations. In this process, sound energy is converted into mechanical energy and thermal energy, and part of the sound energy is dissipated, thereby reducing the intensity of the sound waves passing through and improving the absorption capacity of sound waves. In addition, graphene oxide flakes are evenly distributed on the surface and gaps of glass fibers, and more gaps are formed inside the material, increasing the internal surface area of the material, thereby increasing the friction between the sound waves and the fibers and graphene oxide. The sound waves are converted into heat loss through the viscous friction and heat conduction of the glass fibers and the surrounding graphene oxide microstructures, and the heat is quickly transferred to the outside and released through the high thermal conductivity graphene oxide, thereby improving the sound absorption performance of the material.
[0015] At the same time, graphene oxide can also be coated on the surface of glass fiber to form a dense graphene oxide film. Due to the functional group effect between the two, a strong interface bonding force can be formed, which can improve the rigidity of glass fiber. This increase in rigidity makes the glass fiber less likely to deform or break when subjected to external forces, hinders the expansion of cracks on the surface of glass fiber, thereby improving the mechanical strength of glass fiber and enhancing the bending resistance of fiber felt.
[0016] Polypropylene fibers were prepared by melt phase separation method, in which the micro-nano structure was obtained due to the dissolution of cellulose acetate butyrate, thus achieving sound absorption effect. The polypropylene fibers were dispersed by polyacrylamide solution and then poured on the base felt. The polypropylene fibers overlapped each other on the base felt to obtain a higher porosity, thereby improving the sound absorption and noise reduction effect of the PP fiber / glass fiber felt.
[0017] Optionally, the lower layer of adhesive film comprises polypropylene resin and sound absorption enhancer in a mass ratio of 1:0.1-0.2.
[0018] By adopting the above technical solution and adding a certain amount of sound absorption enhancer to the polypropylene resin, the lower layer of the adhesive film can also have a certain noise reduction and sound absorption effect.
[0019] Optionally, the preparation method of the sound absorption enhancer is as follows: PET chips are mixed with PBT resin and calcium carbonate, melted and spun to obtain PET fibers, which are then immersed in a 5.5-6wt% hydrochloric acid solution for 20-24 hours, filtered, washed and dried to obtain a sound absorption enhancer. The mass ratio of PET resin, PBT resin and calcium carbonate is 1:0.1-0.15:0.03-0.05.
[0020] By adopting the above technical scheme, the PET fiber made by spinning after mixing PET slices with PBT resin and calcium carbonate is immersed in a hydrochloric acid solution, and calcium carbonate is dissolved from the fiber to form more macroscopic micropores. Although the mechanical strength of the fiber will be reduced to a certain extent, the PET fiber will have a certain sound absorption and noise reduction effect. The PBT resin and PET have good compatibility. When blended and spun, the crystallization speed can be accelerated to form a partial copolymer, thereby improving the mechanical properties of the PET fiber. In addition, the PET fiber has high heat resistance. Therefore, after the sound absorption enhancer is added to the polypropylene resin, when it is blended with the polypropylene resin to prepare a film, the fiber shape will not disappear due to heat melting, and the mechanical strength of the polypropylene film can be further improved in the polypropylene film.
[0021] Optionally, the upper adhesive film is a PP adhesive film, and the preparation method of the PP adhesive film is as follows: The polypropylene resin, EPDM particles and nano-silicon dioxide are uniformly mixed in a mass ratio of 1:0.3-0.4:0.04-0.06, and then extruded into granules and injection molded. After hot pressing at 185-190°C for 4-5 minutes and heating at 175-180°C for 20-30 seconds, the mixture is stretched to 0.03-0.04 mm at a speed of 480-500 mm / min, and then cooled to 140-145°C at a speed of 15-20°C / min, and heat-treated at a heat preservation rate of 50-60 minutes.
[0022] By adopting the above technical scheme, nano-silicon dioxide plays a heterogeneous nucleation role in polypropylene, refines the grains, increases the crystallization temperature, accelerates the crystallization rate, effectively improves the toughness of the polypropylene film, and improves the tensile strength and bending properties of the polypropylene film. The EPDM particles and the polypropylene resin have good compatibility, so that the EPDM can be evenly dispersed in the polypropylene matrix to form a tight bond, thereby improving the toughness of the polypropylene film. When the upper polypropylene film is hot-pressed and compounded with the fabric layer, the EPDM can absorb and disperse energy, effectively preventing the rupture of the polypropylene film. Moreover, after the polypropylene resin is mixed with EPDM and nano-silicon dioxide to form granules, the hot-pressed product is subjected to a heat stretching-cooling-annealing heat treatment to make the polypropylene film have a higher initial modulus and a higher elastic recovery rate. The blended melt of propylene resin and EPDM etc. crystallizes under a high tensile stress field to obtain a good melt orientation, thereby forming lamellae arranged in parallel in the stress direction, and thus has good hardness and elasticity; the melt tensile curve of the hot pressed product rises gently after being heated at 175-180°C, which not only ensures the melting of polypropylene etc., but also has a certain strength. The force acting on the melt forms a melt orientation, and when cooled, it can crystallize on the oriented melt to obtain good tensile strength. It is heat treated at 140-145°C, and the high temperature is used to increase the activity of the molecular chain, and the crystallization is improved by adjusting the molecular chain, thereby increasing the crystallinity, improving the thickness of the lamellae, increasing the resilience, and enhancing the tensile strength. Therefore, the polypropylene film is not easy to break due to large deformation when hot-melted, thereby avoiding the occurrence of mottled phenomenon in the fabric layer.
[0023] Optionally, the bottom nonwoven fabric is one of spunlace nonwoven fabric, spunbond nonwoven fabric or heat-rolled nonwoven fabric.
[0024] By adopting the above technical scheme, spunlace non-woven fabrics, spunbond non-woven fabrics, etc. can not only increase the comfort of the car roof, but also have good air permeability, wear resistance, washability, high strength, and can increase comfort and durability.
[0025] In a second aspect, the present application provides a method for preparing a composite material for a car roof, using the following technical solution: A method for preparing a composite material for a car roof comprises the following steps: The maleic anhydride grafted polypropylene and polypropylene resin are mixed, extruded into granules, and cast to prepare a maleic anhydride modified PP film; The PP film, the maleic anhydride modified PP film, the PA film, the maleic anhydride modified PP film and the PP film are sequentially laminated and molded to form a barrier layer; The bottom non-woven fabric, the lower adhesive film, the PP fiber / glass fiber felt, the barrier layer, the upper adhesive film layer and the fabric layer are sequentially laminated, hot-pressed, cooled and cut to obtain the PP glass fiber board.
[0026] By adopting the above technical scheme, maleic anhydride grafted polypropylene is mixed with polypropylene resin and initiator and then cast to obtain maleic anhydride modified PP film, which is then molded with PP film and PA film in sequence to obtain a barrier layer. The bottom layer non-woven fabric, the lower layer film, etc. are then hot-pressed in sequence to obtain a glass fiber board with strong overall stability and not prone to mottle.
[0027] Optionally, the temperature of the compression molding is 160-170° C., and the time is 30-40 seconds; The temperature of the hot pressing molding is 150-160° C. and the time is 35-45 seconds.
[0028] In summary, this application has the following beneficial effects: 1. Since the present application sets a barrier layer between the PP fiber / glass fiber felt and the upper film, and the barrier layer is made of PP film, maleic anhydride modified PP film, PA film, maleic anhydride modified PP film, and PP film, the PP film located in the outermost layer plays a bonding role, and is bonded to the PP fiber / glass fiber felt and the upper film respectively, and the maleic anhydride modified PP film improves the hot melt compatibility of the PA film and the PP film, making the bonding tighter and the overall stability of the barrier layer better. The PA layer plays a role in preventing the diffusion and penetration of small molecules such as additives, preventing the additives in the PP fiber / glass fiber felt from passing through the upper film damaged by hot pressing and forming spots on the car roof fabric layer, which can improve the appearance quality of the car roof.
[0029] 2. In the present application, it is preferred to sequentially impregnate glass fibers with silica sol and graphene oxide, use polypropylene resin and cellulose acetate butyrate to prepare PP fibers with micro-nano pores, and then disperse the PP fibers and pour them on a matrix felt formed by glass fibers, so as to produce PP fiber / glass fiber felt with strong adsorption effect on noise.
[0030] 3. In the present application, it is preferred to prepare a sound-absorbing enhancer by mixing PET chips, PBT resin and calcium carbonate and then impregnating them with a hydrochloric acid solution, which is then mixed with a polypropylene resin to prepare a lower film. The fiber morphology of the sound-absorbing enhancer can improve the mechanical strength of the lower film, thereby enhancing the bending resistance of the glass fiber board, and further enhancing the noise reduction effect of the glass fiber board.
[0031] 4. In the present application, it is preferred to prepare the lower PP film by mixing polypropylene resin with EPDM and nano-silicon dioxide for granulation and then injection molding, and then heat stretching-cooling-annealing heat treatment, so that the toughness and bending resistance of the lower PP film are further improved, so that when the upper PP film is hot-pressed and laminated with the automobile roof fabric layer, it is not easy to be damaged due to large deformation, and thus it can further prevent the automobile fabric layer from producing spots. DETAILED DESCRIPTION
[0032] The following examples further illustrate the present application in detail.
[0033] Preparation Example 1-6 of PP Fiber / Glass Fiber Mat In the following preparation examples, silica sol is selected from Xuancheng Jingrui New Materials Co., Ltd., model VK-S01B, graphene oxide is selected from Shanghai Xiangtian Nanomaterials Co., Ltd., model XT-GO, glass fiber is selected from Taian Hongtong New Materials Co., Ltd., item number 03, length 12 mm, polypropylene is selected from Dongguan Shenghe Plastic, brand 1102L, cellulose acetate butyrate is selected from Shenzhen Yipno Chemical, model CAB-381-20, polyacrylamide is selected from Henan Saike Environmental Protection Technology, molecular weight 3 million.
[0034] Preparation Example 1: 50 g of glass fiber and 50 g of PP fiber were mixed evenly and needle-punched to obtain a PP fiber / glass fiber mat with a thickness of 1 mm. The polypropylene fiber was a commercially available product selected from Shandong Changgu Engineering Materials Co., Ltd. with a product number of A01.
[0035] Preparation Example 2: (1) 50 g of glass fiber was immersed in silica sol, taken out and immersed in an anhydrous ethanol solution of graphene oxide with a concentration of 0.3 wt%, ultrasonicated at a power of 250 W for 120 min, then dried at normal pressure at 55 ° C for 24 h, and needled to obtain a matrix felt; (2) Polypropylene and cellulose acetate butyrate were mixed in a mass ratio of 1:0.2, vacuum dried at 100°C for 24 hours, and then hot-melt spun. The spun material was extracted with acetone as solvent at 60°C for 24 hours to remove the cellulose acetate butyrate in the spinning species, and PP fibers with a length of 60 mm were obtained. The hot-melt spinning temperature was 200°C, the extrusion rate was 100 r / min, and the stretching frequency was 3 Hz. (3) Disperse 50 g of PP fiber into 70 g of 0.1% polyacrylamide solution to obtain a suspension, pour the suspension onto a base felt, vacuum filter, and dry at 60°C to obtain a PP fiber / glass fiber felt with a thickness of 1 mm.
[0036] Preparation Example 3: (1) 50 g of glass fiber was immersed in silica sol, taken out and immersed in an anhydrous ethanol solution of graphene oxide with a concentration of 0.3 wt%, ultrasonicated at a power of 300 W for 100 min, then dried at 50 ° C. under normal pressure for 24 h, and needle-punched to obtain a matrix felt; (2) Polypropylene and cellulose acetate butyrate were mixed in a mass ratio of 1:0.1, vacuum dried at 100°C for 24 hours, and then hot-melt spun. The spun material was extracted with acetone as solvent at 65°C for 20 hours to remove the cellulose acetate butyrate in the spinning species, and PP fibers with a length of 65 mm were obtained. The hot-melt spinning temperature was 200°C, the extrusion rate was 100 r / min, and the stretching frequency was 3 Hz. (3) Disperse 50 g of PP fiber into 60 g of 0.1% polyacrylamide solution to obtain a suspension, pour the suspension onto a base felt, vacuum filter, and dry at 60°C to obtain a PP fiber / glass fiber felt with a thickness of 1 mm.
[0037] Preparation Example 4: The difference from Preparation Example 2 is that the glass fiber is not impregnated with the silica sol, but is directly impregnated with an anhydrous ethanol solution of graphene oxide with a concentration of 0.3 wt %.
[0038] Preparation Example 5: The difference from Preparation Example 2 is that the glass fiber is not impregnated with silica sol and anhydrous ethanol solution of graphene oxide with a concentration of 0.3wt%, and the glass fiber is directly needle-punched to obtain 120g / m 2 Base felt.
[0039] Preparation Example 6: The difference from Preparation Example 2 is that the PP fiber is a commercially available product selected from Shandong Changgu Engineering Materials Co., Ltd. with a product number of A01.
[0040] Preparation Example 7-10 of Sound Absorption Enhancer
[0041] In the following preparation examples, the PET chips were selected from Shanghai Yuanfang, model CH-610, and the PBT resin was selected from Dongguan Juxinheng Rubber & Plastic Co., Ltd., brand 325-1001.
[0042] Preparation Example 7: 100 g of PET chips were mixed with 15 g of PBT resin and 5 g of calcium carbonate, melted and spun at 295°C to obtain PET fibers, which were immersed in a 5.5 wt% hydrochloric acid solution for 24 h, filtered, washed and dried to obtain a sound-absorbing enhancer with a length of 5 mm. During spinning, the extrusion voltage was 70 V, the winding speed was 80 m / min, the spinning plate had 6 holes and a pore size of 0.3 mm.
[0043] Preparation Example 8: 100 g of PET chips were mixed with 10 g of PBT resin and 3 g of calcium carbonate, melted and spun at 295°C to obtain PET fibers, which were immersed in a 6 wt% hydrochloric acid solution for 20 h, filtered, washed and dried to obtain a sound-absorbing enhancer with a length of 5 mm. During spinning, the extrusion voltage was 70 V, the winding speed was 80 m / min, the spinning plate had 6 holes and the pore diameter was 0.3 mm.
[0044] Preparation Example 9: The difference from Preparation Example 7 is that the PET fiber is not immersed in the hydrochloric acid solution.
[0045] Preparation Example 10: The difference from Preparation Example 7 is that no PBT resin is added. Example
[0046] In the following embodiments, the polypropylene resin is selected from Henan Yueqi New Materials Co., Ltd., with the product number PC-GW200, the maleic anhydride grafted polypropylene is selected from Dow, USA, with the model number BYNEL50E662, the EPDM particles are selected from Shanghai Jiuqing Chemical, with the brand number 3702, the PP film with a thickness of 0.03 mm is selected from Dongguan Bailingsi Plastic Technology, with the brand number B-09091 and the product number BLS-BM-040101, the PP film with a thickness of 0.04 mm is selected from Chaozhou Chaoan District Wanxingshun Packaging, with the product number 36, and the PA film is selected from Suzhou Hanruis New Material Technology Co., Ltd., with the product number XJA110 and a thickness of 0.05 mm.
[0047] Example 1: A composite material for a car roof, comprising, from bottom to top, a bottom non-woven fabric, a lower film, PP fiber / glass fiber felt, a barrier layer, an upper film and a fabric layer, wherein the fabric layer is a spunlace non-woven fabric with a thickness of 0.7 mm, the bottom non-woven fabric is a spunlace PET non-woven fabric with a thickness of 0.7 mm, the upper film and the lower film are both PP films, the PP fiber / glass fiber felt is made by Preparation Example 1, and the barrier layer comprises a PP film, a maleic anhydride modified PP film, a PA film, a maleic anhydride modified PP film and a PP film laminated in sequence, and the thickness of the PP films is 0.04 mm.
[0048] The method for preparing the composite material for automobile ceiling comprises the following steps: The polypropylene resin and the maleic anhydride grafted polypropylene were uniformly mixed in a mass percentage of 60% and 40%, respectively, and the mixture was heated to hot melt and then extruded into granules. After hot melt casting at 220° C., a maleic anhydride modified PP film with a thickness of 0.04 mm was obtained. The PP film, the maleic anhydride modified PP film, the PA film, the maleic anhydride modified PP film and the PP film are laminated in sequence and molded to obtain a barrier layer with a thickness of 0.15 mm. The temperature of the molding and laminating is 170° C. and the time is 40 seconds. The spunlace PET non-woven fabric, PP film, PP fiber / glass fiber felt, barrier layer, PP film and fabric layer are laminated in sequence, hot-pressed and then cooled and cut to obtain a PP glass fiber board with a thickness of 2.2 mm. The hot-pressing temperature is 160° C. and the time is 35 seconds.
[0049] Example 2: A composite material for a car roof, comprising, from bottom to top, a bottom non-woven fabric, a lower film, PP fiber / glass fiber felt, a barrier layer, an upper film and a fabric layer, the fabric layer being a spunlace non-woven fabric with a thickness of 2 mm, the bottom non-woven fabric being a spunbond non-woven fabric with a thickness of 2 mm, the upper film and the lower film being both PP films, the PP fiber / glass fiber felt being made by Preparation Example 1, and the barrier layer comprising a PP film, a maleic anhydride modified PP film, a PA film, a maleic anhydride modified PP film and a PP film laminated in sequence, and the thickness of the PP films is 0.03 mm.
[0050] The method for preparing the composite material for automobile ceiling comprises the following steps: The polypropylene resin and the maleic anhydride grafted polypropylene were uniformly mixed in a mass percentage of 60% and 40%, respectively, and the mixture was heated to be molten and then extruded into granules. After hot melt casting at 230° C., a 0.04 mm maleic anhydride modified PP film was obtained. The PP film, the maleic anhydride modified PP film, the PA film, the maleic anhydride modified PP film and the PP film are laminated in sequence and molded to obtain a barrier layer with a thickness of 0.12 mm. The temperature of the molding and laminating is 160° C. and the time is 30 seconds. The spunbond nonwoven fabric, PP film, PP fiber / glass fiber mat, barrier layer and PP film were laminated in sequence, hot-pressed, cooled and cut to obtain a PP glass fiber board with a thickness of 4.5 mm. The hot-pressing temperature was 150° C. and the time was 45 s.
[0051] Example 3: A composite material for automobile ceiling, which is different from Example 1 in that the PP fiber / glass fiber mat is made from Preparation Example 2.
[0052] Example 4: A composite material for automobile ceiling, which is different from Example 1 in that the PP fiber / glass fiber felt is made from Preparation Example 3.
[0053] Example 5: A composite material for automobile roof, which is different from Example 3 in that the PP fiber / glass fiber felt is made from Preparation Example 4.
[0054] Example 6: A composite material for automobile ceiling, which is different from Example 3 in that the PP fiber / glass fiber felt is made from Preparation Example 5.
[0055] Example 7: A composite material for automobile ceiling, which is different from Example 3 in that the PP fiber / glass fiber felt is made from Preparation Example 6.
[0056] Example 8: A composite material for a car roof, which differs from Example 3 in that the upper film is a PP film, and the lower film is made by mixing a polypropylene resin and a sound absorption enhancer in a mass ratio of 1:0.2, melting and casting at 180°C to form a film with a thickness of 0.04 mm. The sound absorption enhancer is made by Preparation Example 7.
[0057] Example 9: A composite material for a car roof, which differs from Example 3 in that the upper film is a PP film, and the lower film is made by mixing a polypropylene resin and a sound absorption enhancer in a mass ratio of 1:0.1, melting and casting at 180°C to form a film with a thickness of 0.04 mm. The sound absorption enhancer is made by Preparation Example 8.
[0058] Example 10: A composite material for automobile ceiling, which is different from Example 8 in that the sound absorption enhancer is prepared from Preparation Example 9.
[0059] Example 11: A composite material for automobile ceiling, which is different from Example 8 in that the sound absorption enhancer is made from Preparation Example 10.
[0060] Example 12: A composite material for automobile ceiling, which is different from Example 8 in that the sound absorption enhancer is diatomaceous earth selected from the Zhongshi Keyuan mine product in Lingshou County, model 300.
[0061] Embodiment 13: A composite material for automobile roof, which is different from Embodiment 8 in that the PP film on the upper layer is made by the following method: 70g of polypropylene resin, 28g of EPDM particles and 4.2g of nano-silicon dioxide were mixed evenly, then heated and melted for extrusion granulation and injection molding. The sheets with a thickness of 1mm were made by hot pressing at 185°C for 5min, then heated at 175°C for 30s, stretched to 0.04mm at a speed of 480mm / min, then cooled to 140°C at a rate of 15°C / min, and heat-treated for 60min to obtain PP film. The extrusion granulation temperatures were: 100°C for zone 1, 120°C for zone 2, 140°C for zone 3, 180°C for zone 4, 195°C for zone 5, 195°C for zone 6, and 185°C for die head. The injection molding temperatures were: 200°C for zone 1, 195°C for zone 2, 175°C for zone 3, 70MPa for pressure, and 19s for holding time.
[0062] Embodiment 14: A composite material for automobile roof, which is different from Embodiment 8 in that the upper film is a PP film, and the PP film is made by the following method: 70g of polypropylene resin, 21g of EPDM particles and 2.8g of nano-silicon dioxide were mixed evenly, then heated and melted for extrusion granulation and injection molding. A sheet with a thickness of 1mm was made by hot pressing at 190°C for 4min, then heated at 180°C for 20s, stretched to 0.04mm at a speed of 500mm / min, then cooled to 145°C at 20°C / min, and heat-treated for 50min to obtain a PP film. The extrusion granulation temperature was: 100°C for zone 1, 120°C for zone 2, 140°C for zone 3, 180°C for zone 4, 195°C for zone 5, 195°C for zone 6, and 185°C for die head. The injection molding temperature was: 200°C for zone 1, 195°C for zone 2, 175°C for zone 3, the pressure was 70MPa, and the holding time was 19s.
[0063] Example 15: A composite material for automobile roof, which differs from Example 13 in that no nano-silicon dioxide is added.
[0064] Example 16: A composite material for automobile ceiling, which differs from Example 13 in that EPDM is not added.
[0065] Example 17: A composite material for automobile ceilings, which differs from Example 13 in that polypropylene resin, EPDM particles and nano-silicon dioxide are mixed, extruded into granules, and then hot-melt cast at 200°C to form a PP film with a thickness of 0.04 mm.
[0066] Comparative Example
[0067] Comparative Example 1: A composite material for automobile ceiling, which differs from Example 1 in that no barrier layer is provided.
[0068] Comparative Example 2: A composite material for automobile ceiling, which differs from Example 1 in that no maleic anhydride-modified PP film is provided on both sides of the PA film, and the barrier layer only includes a PP film, a PA film and a PP film laminated in sequence.
[0069] Comparative Example 3: A composite material for automobile ceiling, which differs from Example 1 in that a PP film is used to replace the PA film in the barrier layer, and the barrier layer is a PP film, a maleic anhydride-modified PP film, a PP film, a maleic anhydride-modified PP film and a PP film bonded to each other.
[0070] Performance testing
[0071] The composite material for automobile ceiling was prepared according to the methods in the examples and comparative examples, and its performance was tested according to the following methods. The test results are recorded in Table 1.
[0072] 1. Ratio of spot area: Hot-press the prepared fiberglass board and the non-woven fabric layer of the car roof, and observe the ratio of spots on the same area.
[0073] 2. Flexural strength: The test was carried out in accordance with GB / T3356-2014 "Test method for flexural properties of oriented fiber reinforced polymer matrix composites". Five points were taken for testing for each sample, and the results were averaged.
[0074] 3. Sound insulation: Test in accordance with GB / T18696.1-2004 "Measurement of sound absorption coefficient and acoustic impedance in acoustic impedance tubes Part 1: Standing wave ratio method".
[0075] Table 1 Performance test of composite materials for automobile roof
[0076] From the test data in Examples 1-2, Comparative Example 1 and Table 1, it can be seen that after adding a barrier layer to the glass fiber board, the diffusion of antioxidant additives in the PP fiber / glass fiber felt can be effectively blocked, thereby reducing the occurrence of spots on the car roof fabric layer and improving the appearance quality of the car roof fabric layer.
[0077] Compared with Example 1, Examples 3 and 4 respectively use the PP fiber / glass fiber felt prepared in Preparation Example 2 and Preparation Example 3. Table 1 shows that after the PP glass fiber board composite fabric layer prepared in Examples 3-4 is formed, the pattern area does not change much, but its sound absorption and sound insulation effect is significantly enhanced, and the bending strength is increased.
[0078] In Example 5, the PP fiber / glass fiber felt prepared in Preparation Example 4 is used. Compared with Example 3, the glass fiber is not impregnated with silica sol. It can be seen that the sound absorption capacity of the prepared PP glass fiber board is reduced, and the sound insulation is reduced.
[0079] Compared with Example 3, Example 6 uses the PP fiber / glass fiber felt prepared in Preparation Example 5, wherein the glass fiber is not impregnated with silica sol and anhydrous ethanol solution of graphene oxide. The sound insulation of the PP glass fiber board prepared in Example 6 is significantly reduced, and the bending strength is decreased, indicating that the pretreatment of the glass fiber can effectively enhance the noise reduction, sound absorption and bending resistance effects of the PP glass fiber board.
[0080] In Example 7, the PP fiber / glass fiber felt prepared in Preparation Example 6 was used, and a suspension was prepared using commercially available polypropylene fiber, which was then poured onto a base felt. Compared with Example 3, the sound insulation was reduced and the bending strength was decreased, indicating that the polypropylene fiber prepared in this application had a certain sound insulation effect and was more resistant to bending.
[0081] Compared with Example 3, in Example 8 and Example 9, although the upper layer of the film is still a PP film, a fibrous sound-absorbing enhancer is added to the lower layer of the film. The sound-absorbing enhancer is made by mixing PET, EV and calcium carbonate, spinning, and impregnating hydrochloric acid. It can be seen that the PP glass fiber board made in Example 8 and Example 9 has further increased sound insulation, enhanced noise reduction and sound absorption effects, and increased bending strength.
[0082] In Example 10, the sound absorption enhancer prepared in Preparation Example 9 was used. Compared with Preparation Example 7 in Example 8, the sound absorption enhancer was not immersed in the hydrochloric acid solution. It can be seen that the bending strength of the prepared PP glass fiber board did not change much, but the sound absorption effect decreased.
[0083] In Example 11, the sound absorption enhancer prepared in Preparation Example 10 was used. Compared with Preparation Example 8, no PBT resin was added. It can be seen that the bending resistance of the glass fiber board is reduced, and the sound absorption effect does not change much.
[0084] In Example 12, diatomaceous earth is used as a sound absorption enhancer. Compared with Example 9, the sound absorption effect is reduced, and the bending resistance and anti-mottling capabilities do not change much. It can be seen that the noise reduction effect of the polypropylene film prepared by adding diatomaceous earth to polypropylene is not as good as the sound absorption enhancer of the present application.
[0085] Compared with Example 8, the upper layer of the adhesive film in Examples 13 and 14 is made of a mixture of polypropylene resin, EPDM, and nano-silicon dioxide, and then subjected to heat stretching, cooling and annealing heat treatment. It can be seen from the data in Table 1 that the mottling problem of the PP glass fiber board prepared in Examples 13-14 and the fabric layer after hot pressing is further improved, indicating that the bending and deformation resistance of the upper layer of the adhesive film is increased, and the bending resistance of the glass fiber board is enhanced.
[0086] Compared with Example 13, in Examples 15 and 16, no nano-silicon dioxide and EPDM particles were added when preparing the upper PP film. The data in Table 1 show that the PP glass fiber boards prepared in Examples 15-16 have decreased bending resistance and a slightly increased pattern area compared with Example 13, but the sound insulation does not change much.
[0087] In Example 17, polypropylene resin is mixed with EPDM and nano-silicon dioxide and then cast into a film without heat stretching and other treatments. From the comparison of data in Table 1, it can be seen that compared with Example 13, the bending strength of the PP glass fiber board prepared in Example 16 is reduced and the spot area is increased.
[0088] In Comparative Example 2, no maleic anhydride-modified PP film was added, and in Comparative Example 3, PP film was used instead of PA film. Table 1 shows that, compared with Example 1, the glass fiber boards prepared in Comparative Examples 2 and 3 did not significantly improve the mottling problem of the automobile roof.
[0089] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A composite material for automobile ceiling, characterized in that: It comprises a bottom non-woven fabric, a lower adhesive film, PP fiber / glass fiber felt, a barrier layer, an upper adhesive film and a fabric layer in sequence. The barrier layer is made by compression molding of a PP adhesive film, a maleic anhydride modified PP film, a PA film, a maleic anhydride modified PP film and a PP adhesive film in contact with each other in sequence.
2. The composite material for automobile ceiling according to claim 1, characterized in that: The thickness of the barrier layer is 0.12-0.15 mm.
3. The composite material for automobile ceiling according to claim 1, characterized in that: The PP fiber / glass fiber mat contains PP fibers and glass fibers in a mass ratio of 1:
1.
4. The composite material for automobile ceiling according to claim 3, characterized in that: The preparation method of the PP fiber / glass fiber mat is as follows: The glass fiber is immersed in silica sol, taken out and immersed in an anhydrous ethanol solution of graphene oxide, ultrasonicated at a power of 250-300W for 100-120min, then dried at 50-55°C under normal pressure, and needled to obtain a matrix felt; The polypropylene and cellulose acetate butyrate are mixed in a mass ratio of 1:0.1-0.2, and the mixture is melt-spun after vacuum drying. The spun product is extracted at 60-65° C. for 20-24 hours using acetone as a solvent to obtain PP fiber. The PP fiber is dispersed in the polyacrylamide solution to obtain a suspension, and the suspension is poured on a base felt, vacuum filtered and dried to obtain a PP fiber / glass fiber felt.
5. The composite material for automobile ceiling according to claim 1, characterized in that: The lower layer of adhesive film comprises polypropylene resin and sound absorption enhancer in a mass ratio of 1:0.1-0.
2.
6. The composite material for automobile ceiling according to claim 5, characterized in that: The preparation method of the sound absorption enhancer is as follows: PET chips are mixed with PBT resin and calcium carbonate, melted and spun to obtain PET fibers, which are then immersed in a 5.5-6wt% hydrochloric acid solution for 20-24 hours, filtered, washed and dried to obtain a sound absorption enhancer. The mass ratio of PET resin, PBT resin and calcium carbonate is 1:0.1-0.15:0.03-0.
05.
7. The composite material for automobile ceiling according to claim 1, characterized in that: The upper film is a PP film, and the preparation method of the PP film is as follows: The polypropylene resin, EPDM particles and nano-silicon dioxide are uniformly mixed in a mass ratio of 1:0.3-0.4:0.04-0.06, and then extruded into granules and injection molded. After hot pressing at 185-190°C for 4-5 minutes and heating at 175-180°C for 20-30 seconds, the mixture is stretched to 0.03-0.04 mm at a speed of 480-500 mm / min, and then cooled to 140-145°C at a speed of 15-20°C / min, and heat-treated at a heat preservation rate of 50-60 minutes.
8. The composite material for automobile ceiling according to claim 1, characterized in that: The bottom nonwoven fabric is one of spunlace nonwoven fabric, spunbond nonwoven fabric or hot-rolled nonwoven fabric.
9. The method for preparing the composite material for automobile ceiling according to any one of claims 1 to 8, characterized in that: The following steps are involved: The maleic anhydride grafted polypropylene and polypropylene resin are mixed, extruded into granules, and cast to prepare a maleic anhydride modified PP film; The PP film, the maleic anhydride modified PP film, the PA film, the maleic anhydride modified PP film and the PP film are sequentially laminated and molded to form a barrier layer; The bottom non-woven fabric, the lower adhesive film, the PP fiber / glass fiber felt, the barrier layer, the upper adhesive film layer and the fabric layer are sequentially laminated, hot-pressed, cooled and cut to obtain the PP glass fiber board.
10. The method for preparing the composite material for automobile ceiling according to claim 9, characterized in that: The temperature of the compression molding is 160-170°C and the time is 30-40s; The temperature of the hot pressing molding is 150-160° C. and the time is 35-45 seconds.
Citation Information
Patent Citations
Production method of low-gram-weight high-intensity automobile inner trim ceiling
CN103434253A
Novel vehicle roof and production process thereof
CN103921504A
Automobile roof and manufacturing method thereof
CN104309234A
PP fiberglass panel car roof and production method thereof
CN104369775A
Method for producing automotive interior ceiling
CN107672239A
Cited By
Glass fiber modified automobile composite material and preparation method thereof
CN120287709A